Successful Treatment of Localized Pemphigus Foliaceus with Topical Pimecrolimus - G. Tyros; K. Kalapothakou; E. Christofidou; A. Kanelleas; P. G. Stavropoulos (Hindawi Limited, 2013)
We report the case of successful treatment of a 79-year-old male patient with recurrent pemphigus foliaceus with pimecrolimus cream 1% once daily for 40 days. The patient initially presented with localized lesions on the scalp and nose area and was treated with systemic corticosteroids. At his fourth relapse within a period of 16 months, he refused any systemic treatment. Pimecrolimus cream was suggested to him as an alternative option.